ON THE ACCOUNTING OF RESERVE CAPITAL IN LIMITED LIABILITY COMPANIES - Biriuk , Olena; Kotsupatryi , Mykhailo; Melnychuk , Viktoriia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article explores the theoretical and legal foundations for the formation and accounting of reserve capital in limited liability companies (LLCs). Special attention is paid to the peculiarities of creating a targeted reserve for the acquisition of shares in the company’s own charter capital without reducing its size, as provided by current Ukrainian legislation. The feasibility of detailing account 43 through the introduction of subaccounts 431 and 432, depending on the purpose of use, is substantiated. A proposed set of accounting entries ensures transparency, compliance with the company’s charter, and effective profit management.